Analysis of COVID-19 vaccine type and adverse effects following complete vaccination - Mansoor, Sarah; Nawaz, Muhammad Hashim; Butt, Hira; Chheena, Ayesha; Zahid, Amina; Nasir, Maham (Infectious Diseases Journal of Pakistan, 2024)
Backgrounds: Immunization is one of the most successful and cost-effective health interventions to prevent infectious diseases. The launch of the COVID-19 vaccine rollout in December 2020 was a landmark for overcoming this pandemic crisis. It is therefore very important to get most of the population vaccinated as definitive cure still does not exist and people must take all required doses on time as required to reach full immunity. To find the association between covid-19 vaccine type and adverse effects following complete vaccination. Material and Methods: This Cross-sectional study was conducted in Sharif Medical and Dental College, Lahore over a period of one year from January 2022 to January 2023 on a total of 100 individuals. All participants irrespective of their age and gender were included in the study. Participants with any other systemic illness or those on medication for other illnesses were excluded from the study. Data was collected using a pre-validated questionnaire Results: The association between the type of vaccine and post-vaccination symptom were significant for fever (p=0.018) and cough (p=0.015). Conclusion: Fever and cough were most prevalent among individuals who received Sinovac. Most of the symptoms were more prevalent in Sinovac recipients as compared to Sinopharm. Post-vaccination COVID-19 infection was also more prevalent in those who received Sinovac. Keywords: COVID-19 infection, COVID-19 vaccination, Side effects